Analisis Hubungan Akreditasi Rumah Sakit dengan Penetapan Rujukan Covid-19 di DKI Jakarta - Ricky Fathoni; Adang Bachtiar (Syntax Literate, 2022)
World Health Organization (WHO) declared Coranavirus Desease 2019 (COVID-19) was pandemic on march 11, 2020. In Indonesia, the number of hospitals that have been nationally accredited and designated as COVID-19 referrals by the Governor of DKI Jakarta are 86 hospitals. Accreditation will assist hospitals in the COVID-19 pandemic by preparing and implementing clinical guidelines in the form of Clinical Practice Guidelines. This study aims to see the relationship between accreditation status and the establishment of a COVID-19 referral hospital in DKI Jakarta. The study used a cross-sectional method by looking at the relationship between the accreditation status of hospitals in DKI Jakarta and the establishment of a referral hospital for COVID-19 prevention. The analyzed data are accreditation status according to levels. The sampling technique is purposive sampling. The results of the binary logistic regression analysis of accreditation status were associated with the designation of a referral hospital in DKI Jakarta (p: <0.001). The results of the analysis obtained that the more accreditation status, the higher the chance to be designated as a referral hospital. All accredited hospitals are expected to be able to provide COVID-19 services according to the standards set by the government.